Conceptualizing commitment to quality in an elementary school: Factor analysis of the effect of communication on employee attitudes and behaviours for Quality Management - Lavoie, Carine (University of Ottawa (Canada), 2007)
Although the literature establishes the importance of employee commitment and communication, there is a lack of empirical research focusing on communication's precise role for Quality Management (QM). Within the context of change, this thesis demonstrates that communication contributes to commitment by targeting both attitudes and behaviours. These findings were used to build a content analysis identified communication initiatives within a school's QM program and an interview linked those initiatives to desired changes in attitudes and in behaviours to build an employee survey assessing communication and commitment. A factorial analysis revealed that three communication factors -- Involvement, Learning Culture and Formal Communication -- contributed to changes in both attitudes and behaviours suggesting that organizations can emphasize these factors in their communication plans to set the foundation for commitment to quality. This study focuses on the role of communication in creating commitment to quality specifically through attitudes and behaviours. Future research would be valuable in validating this model within other types of organizations.
Keywords: Education, Administration.; Education, Elementary.; Mass Communications.